ANALISA KUAT HANTAR ARUS KABEL TANAH 150 kV YANG MELINTASI JEMBATAN - Redaksi Tim Jurnal (Energi & Kelistrikan, 2015)
The use of underground cables in transmission lines and the distribution of today is increasing rapidly, especially in urban and industrial areas. Electrical power supply between 150 kV substation using a cable. When cables pass through unfavorable as paved areas and bridges, then decrease the heat transfer from the cable to the environment. The heat will accumulate resulting in temperature rise, so capability of ground wire current-carrying wires must be lowered so that the ground is not damaged due to limited working temperature insulating materials. This research will discuss the current-carrying strength analysis of 150 kV land cables that cross the bridge.